Peer Review in Improving Students’ Perception Argumentative Essay: The Effectives from Students’ Perceptive - Feby Annisa Yasmin; Nurasiah Anggini; Rizki Putri Jasmine Siahaan (Universitas Muhammadiyah Enrekang, 2023)
Peer review is a well-known technique for raising students' writing standards. By evaluating the peer-review process, this study goes beyond its initial focus on results. This study specifically focuses on the timing of peer review, a highly organized feedback form, and student writers' changes following peer review. According to the research, these techniques assist students provide formative input to their classmates, drive them to start writing earlier in the semester, and motivate them to significantly edit their drafts before turning in their final papers. This study highlights how crucial it is to evaluate the peer-reviewing procedure. This conclusion was obtained after examining students' replies on a questionnaire that included closed option (multiple choice) questions as well as open-ended comments on the same three aspects of the impact of peer review: critical thinking, collaborative work, and composition quality. This study is based on Vygotsky's sociocultural approach and supports and broadens earlier research on the subject by providing a more in-depth and comprehensive viewpoint. Participants who have utilized this methodology comment on its advantages and/or disadvantages.